King jack and the dragon eaudiobook - Bently, Peter (Recorded Books Inc., 2012)
Peter Bently's unique mix of rhyming verse, storytelling, and humor is a surefire hit with young readers. In King Jack and the Dragon, Jack, his toddler brother Caspar, and his friend Zack build a make-believe fort capable of stopping the attacks of fire-breathing dragons and all sorts of other beasties. But as playtime draws to a close and his knights get carried away by marauding parents, Jack discovers that defending a magical fort is more fun with a few friends.